THE VALUE OF AIR GERM NUMBERS AT SOEKARNO HATTA AIRPORT IN 2021 - Ida Riani Natalis Siringo-Ringo; Erna Veronika; Mugi Wahidin; Devi Angeliana Kusumaningtiar (Universitas Airlangga, 2022)
Introduction: Indoor air quality greatly affects human health, because almost 90% of human life is indoors. This study aims to analyze the number of airborne germs at Soekarno Hatta Airport in 2021. Methods: The research design was cross-sectional study. The number of measurements of airborne germ numbers was carried out in 29 locations with 136 sample points, and mapping was carried out at 20 locations with 78 sample points. Data collection was using secondary data from Port Health Office of Class I Soekarno Hatta. The analysis used is univariate analysis, presented in the form of a frequency distribution table and mapping with ArcGIS and AutoCad. Results and Discussion: The study showed that most of the airborne germ numbers matched the quality standard, but there were 14 sample points (10.3%) that exceeded the quality standard. High-risk locations with red zones are located at Domestic Terminal 3 and Port Health Office of Class I Soekarno Hatta. Low-risk locations with green zones are in International Terminal 3 and Terminal 2. Conclusion: Therefore, all building, bus, and airline managers need to improve implementation disinfection, cleaning of the entire area, periodic maintenance of air conditioner and replacement of Hepafilter. Measurement of air germ numbers is needed as a routine activity of Port Health Office of Class I Soekarno Hatta to evaluate and monitor air quality